Assessing the factors militating against the effective implementation of electronic health records (EHR) in Nigeria - Abisola Esther BABATOPE; Idowu Peter ADEWUMI; Damola Olanipekun AJISAFE; Kayode Olayiwola ADEPOJU; Adetola Rachael BABATOPE (Scientific Reports)
Abstract This study assessed the factors militating against the effective implementation of electronic health records (EHR) in Nigeria, the computerization of patients’ health records with a lot of benefits including improved patients’ satisfaction, improved care processes, reduction of patients’ waiting time, and medication errors. Despite these benefits, healthcare organizations are slow to adopt the EHR system. Therefore, the study assessed the factors militating against the effective implementation of the EHR system, the level of awareness of EHR, and the utilization of electronic health records; it also investigated the factors militating against the effective implementation of EHR. This is a descriptive cross-sectional study conducted among members of staff of the University of Medical Sciences Teaching Hospital (UNIMEDTH). Purposive sampling was adopted to select the study participants, and a structured questionnaire was used for data collection. Statistical Product and Service Solutions (SPSS) version 27 was used for data analysis, R and Microsoft Excel were used for data visualization. Findings revealed that the respondents had a high level of awareness of EHR with an average mean of 1.29. The study revealed a low utilization rate for EHR (mean 3.01, SD 0.115) and data storage (mean 3.00, SD 0.231), indicating major problems with EHR implementation. Financial limitations (mean 2.63, SD 0.486) and insufficient ICT resources (mean 2.62, SD 0.516) are the main challenges. The regression analysis revealed that EHR utilization is highly impacted by awareness (F = 4.26, p < 0.008), accounting for 15.1% of the variance. Governmental assistance and financial constraints showed a statistically significant negative correlation (r=−0.04, p < 0.05), while inadequate internet connectivity and epileptic power supply showed a statistically significant positive association (r = 0.1, p < 0.05). The results show that, more government support is needed to alleviate financial constraints, and a stable power supply may enhance internet accessibility. The study concluded that epileptic power supply, poor internet connectivity, financial constraints, and other factors mentioned in the study militate against the effective implementation of electronic health records. It was recommended that the management should implement electronic health records effectively for efficient and effective health care delivery.